Cultivating collaborative adaptability in public lands social-ecological settings: linking theory, practice, and evaluation across cases and contexts - Beeton, Tyler Andrew, author; Galvin, Kathleen, advisor; Cheng, Antony, committee member; Schultz, Courtney, committee member; Snodgrass, Jeffrey, committee member (Colorado State University. Libraries, 2024)
Collaborative and adaptive forms of governance have become increasingly common in environmental management as they are claimed to help reduce conflict over resource management issues and uncertainty, increase trust, support shared understanding and buy-in for management actions, and facilitate social learning. In the USDA Forest Service, legal, regulatory, and bureaucratic challenges, and the increased emphasis on ecosystem management has increased the demand for, and investment in, collaboration as a tool to meet forest and fire management goals. Collaborative governance and adaptability scholarship has documented the key drivers and external conditions that influence collaboration, the internal dynamics that cultivate or constrain collaboration, and the outputs and outcomes of collaboration. Still, a number of research gaps remain that, if addressed, could advance the theory and practice of collaborative governance. First, the ways in which groups adapt and remain resilient to inevitable internal and external changes remains underexplored. Second, despite over twenty years of research in this space, relatively little is known about the configuration of, and relationship between, factors that comprise collaborative governance and adaptability. Third, collaboration is dynamic. As groups evolve, they create value in different ways, and their needs and priorities change. Thus, there is a need for periodic and ongoing assessments of how collaboration is working in local contexts, current challenges, and what adaptations are needed to improve collaborative processes and progress. This dissertation starts to address these research gaps and needs. I situated this work within the Collaborative Forest Landscape Restoration Program, a Forest Service-administered program first authorized in 2009 and reauthorized in 2019. The work presented in this dissertation was co-developed with the Southwest Ecological Restoration Institutes and the Forest Service Forest, Range Management, and Vegetation Ecology Program. Specifically, the work supported synthesis of lessons learned from the first 10 years of the CFLRP and the development of a standardized and longitudinal assessment of collaborative governance and adaptability for use in the CFLRP Common Monitoring Strategy. Broadly, my dissertation contributes to our understanding of the factors that facilitate or frustrate adaptation to inevitable change in collaborative settings. This is a critical line of inquiry given the increased and sustained investment in long-term collaborative environmental management in the United States and beyond. I employed a mixed-method analysis consisting of focus groups, program-wide surveys, and a systematic review, and I drew on the Integrative Framework for Collaborative Governance, collaborative adaptability and resilience literature, and organization theory to frame my analysis. In Chapter 2, I asked, how do collaborative governance regimes adapt to disruptions and what barriers constrained collaborative resilience? I found that collaboratives demonstrated the ability to mobilize social capital, learning, resources, and flexibility to respond to disruptions. Yet authority, accountability, and capacity complicated collaborative resilience. I conclude Chapter 2 with policy and practice recommendations to cultivate collaborative resilience moving forward. In Chapter 3, I developed and deployed a program-wide collaborative governance and adaptability assessment to all currently authorized CFLRP projects. I used a modified grounded theory approach to document and describe CFLRP project respondents' recommended actions and adaptations to improve collaborative processes and progress towards desired outcomes. Key recommendations included the need for: inclusive engagement throughout the process; institutional arrangements; resources and capacity; monitoring and social learning; trust, relationships, and commitment; external communication and outreach; and local autonomy in decision making. I discussed these findings in light of collaborative governance theory and practice and included relevant resources and actions that practitioners and funders of collaboratives and policy actors may consider to support collaboratives in working towards forest and fire management objectives. In chapter 4, I again used the program-wide CFLRP collaborative governance and adaptability assessment, and I used confirmatory factor analysis to test assumptions underlying the dimensional structure, reliability, and validity of measures thought to comprise collaborative governance and adaptability. I found that the components of collaborative governance and adaptability comprised six dimensions – principled engagement, shared motivation, leadership, resources, knowledge and learning, and institutional arrangements. As expected, several dimensions were significantly related, and the pattern of inter-factor relationships aligned with theoretical and empirical assumptions. We also found that the six dimensions represent statistically reliable, valid, and distinct measures that may be used to evaluate collaborative governance and adaptability. While our focus was on the CFLRP, the assessment can be adapted to other collaborative environmental governance contexts. Chapter 5 ends with a summary of findings, limitations of the work, and future research directions to address lingering questions about collaborative environmental governance.
Keywords: Collaborative Forest Landscape Restoration Program; confirmatory factor analysis; resilience; collaborative governance; adaptability; qualitative methods